Electrochemical faceting and preferred cyrstallographic orientation of rhodium electrodes - Custidiano, Ernesto Ramón (1987)
The electrochemical faceting of Rh in 1 M H2SO4 can be developed by applying repetitive periodic potentials in the range −0.1 to 1.2 V (vs. RHE) at frequencies greater than 0.5 kHz. The degree of electrochemical faceting, as followed voltammetrically at 0.1 V/s in the H-adatom potential range, exhibits two different situations, depending on the lower and upper limits of the periodic potential. In one case the voltammogram exhibits two sharp reversible conjugated peaks related to the H-adatom reactions, similar in shape to those reported for Rh (111), although the peak potentials are closer to those found for Rh (110). In the other case, a complex voltammogram is obtained which can be related to a predominance of (111) and (100) crystallographic faces. SEM micrographs confirm the development of electrochemical faceting involving steps, terraces and pyramidal structures which are related to the preferred orientations.